Morbidity in elderly women undergoing gynaecological pelvic floor surgery - Tuschy, Benjamin; Berlit, Sebastian; Hornemann, Amadeus; Sütterlin, Marc; Bussen, Stefanie (Archives of gynecology and obstetrics, 2012)
Purpose: We investigated the morbidity in elderly patients undergoing surgery due to pelvic organ prolapse. Methods: Perioperative data of 113 patients aged at least 50 years who underwent gynaecological prolapse surgery between 2005 and 2011 were analyzed retrospectively. Forty-eight women were older than 70 years and matched our inclusion criteria. Sixty-five patients aged 50-69 years undergoing similar surgical procedures during the same period of time formed the control group. Operating time, duration of hospital stay, intra- and postoperative complications, comorbidity, and body mass index were evaluated. Results: There were no significant differences between study and control collective regarding operating time, duration of hospital stay, intra- and postoperative complications, and body mass index although a significant difference could be notified between the pre-existing comorbidity. Conclusion: Surgery due to a pelvic organ prolapse in patients aged more than 70 years is a feasible and save treatment to improve quality of life in elderly patients.